Pengembangan Sistem Informasi Model Pembelajaran Berbasis Teknologi Menggunakan Metode ADDIE di SMP Wee Manada - Marlince Wilpa; Ardiyanto Dapadeda; Sihang Gregorius Balimema (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
SMP Wee Manada still relies on conventional, manual methods to distribute learning materials, a condition that prompted this study. Such practices have led to the loss of physical archives, difficulties in organizing assignments, and restricted access to learning resources among students. This study aims to develop an integrated technology-based information system that enables administrators, teachers, and students to interact more efficiently within an educational setting. The Research and Development (R&D) method was applied alongside the ADDIE development model, which consists of five sequential stages: analysis, design, development, implementation, and evaluation. The results demonstrate that the core features of the information system operate correctly and reliably. These features include the publication of teaching materials, student data management, and a real-time assignment submission and assessment system. Black Box Testing was conducted to verify that the system runs accurately and consistently. Through the adoption of this system, SMP Wee Manada is positioned to establish a clearer and more accessible digital learning environment for all students